(untitled) (American Journal of Islam and Society, 1994)
The market (suq or Bazar)has a distinctive place in the history of Islamic civilization. Makkah and MadInah were major trade centers at the time of the advent of Islam, and the prophet was himself an active market participant and reformer. There were famous markets-’Ukkaz, Majannah, and Dhu al Majaz- in pre-Islamic Arabia that commonly held fairs during the pilgrimage season. This practice was conhued after the appearance of Islam, for when the new Muslims felt that it might be sinful for them to trade in such places (al Zubayli 1984), the following verse was revealed: "There is no sin if you seek the bounty of your Lotd (during the pilgrimage)" (Qur’an 2:198). The main theme here is religious: allaying the fear of indulging in sin. However, it is Significant that this potentially sinful activity was ref e d to in such dignified term as "seeking the bounty of your Lotd." Elsewhere in the Qur’an, we find passages dealing withthe market’s cultural Elspects, such as the verse that asks whether it is proper for the Prophet to mingle with the common people in the market place. The answer received was that prophets, just like everybody else, ate free to interact and engage in commercial tnmsactions in the mark& "And they say: What sort of a messenger is this, who eats food and walk- through the streets? Why has not an angel been sent down to him to be a Warner with him?" (Qur’an 257) and "And the Messengers whom We sent before you were all (men) who ate food and walked through the streets" (Quran 25:20). The second citation refers to market activity in a mainly econofnic and historical context, one that highlights the market’s role in providing foodstuffs and the fact that all prophets mixed with their people on the basis of equality. In other words, they were ordinary men whose spiritual value was not compromised by engaging in market activities. These verses characterize Islam’s worldview in gened and its view of the market’s diverse nature in particular. Islam reaffirms its holistic approach to life and informs us that the market is an arena for the combined interplay of culture, religion, economics, and history. This was partly due, perhaps, to the Prophet’s own commercial experience and acumen, which he put to good use as his future wife’s (Khadijah) trusted agent and that led eventually to the reform of Arabian commercial practices. These reforms sought to purify the market of practices that differed from Islamic ideals of fair play, honesty, and justice. In many ways, a market is like an open theater, for it displays the unfolding of a portion of a civilization’s best achievements as well as its worst weaknesses and pitfalls. One frequent issue is the need to recognize the free market principle: the goveming of trade solely by the natural interplay of the economic forces of supply and demand. Only in such a market, it is argued, is one urged to strive and compete with his/her peers in pursuit of better products or services. No market can exist without a profit motive, and the right to make a profit must never be eliminated. Thus a market regulator must be concerned with asceltaining that legitimate profit does not exceed the limits of fair gain and that an individual’s greed and desire for profit are controlled. The intention is to ensure that skilled market operators do not take advantage of an unsuspecting customer’s ignorance and naivety. Broadly speaking, one may say that this was the main goal of the new Islamic rules introduced into the Arabian market’s economic life. No law dealing with the quantitative limits of profit was promulgated, for profit is the result of supply and demand and so is not a concern of the law. The law’s role is limited to ensuring the market’s morality, as well as the propriety and fairness of its participants and their activities (i.e., prohibiting fraud and misrepresentation), and implementing precautionary measures to prevent or rectify unfair trading practices ...